Review artikel : pemanfaatan bahan alam pada sediaan face mist - Rahmadasmi, Nola; Wulandari , Desti; AH , Ahdi Dinil Haq. (Journal of Pharmaceutical and Sciences, 2024)
This article review aims to review several journals that formulate face mist preparations by utilizing natural ingredients. Some of the natural ingredients used have a variety of beneficial properties for the skin, especially the face such as facial moisturizers, antioxidants and antibacterials. Face mist is included in cosmetics that are efficacious as skin refreshers, especially to refresh facial skin and can remove residual oil from the skin that may still exist. Refreshers are made according to the type of cleanser that refers to the type of skin on the face. Face mist preparations have advantages when compared to other preparations including easy to use and carry anywhere, and more quickly absorbed into the skin. The formula used is a variation of the concentration of the active substance (sample) with additional substances such as glycerin as a moisturizer and PVP (polyvinyl pyrrolidone) as a dispersing agent and preservatives in the form of nipagin, nipasol, DMDM Hydantoin and sodium benzoate and distilled water as a carrier (solvent).